THEORETICAL ISSUES OF MECHANISMS FOR FORMING STRATEGIES FOR THE SOCIO-ECONOMIC DEVELOPMENT OF REGIONS - Mamatxonov Muxammadzokir Juraboyevich (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2024)
This article presents ideas and considerations on the theoretical issues of the mechanisms for forming a strategy for the socio-economic development of regions.